Validation of Current Good Manufacturing Practice Compliant Human Pluripotent Stem Cell-Derived Hepatocytes for Cell-Based Therapy. (19th November 2018) - Blackford, Samuel J.I.; Ng, Soon Seng; Segal, Joe M.; King, Aileen J.F.; Austin, Amazon L.; Kent, Deniz; Moore, Jennifer; Sheldon, Michael; Ilic, Dusko; Dhawan, Anil; Mitry, Ragai R.; Rashid, S. Tamir
Abstract: Recent advancements in the production of hepatocytes from human pluripotent stem cells (hPSC-Heps) afford tremendous possibilities for treatment of patients with liver disease. Validated current good manufacturing practice (cGMP) lines are an essential prerequisite for such applications but have only recently been established. Whether such cGMP lines are capable of hepatic differentiation is not known. To address this knowledge gap, we examined the proficiency of three recently derived cGMP lines (two hiPSC and one hESC) to differentiate into hepatocytes and their suitability for therapy. hPSC-Heps generated using a chemically defined four-step hepatic differentiation protocol uniformly demonstrated highly reproducible phenotypes and functionality. Seeding into a 3D poly(ethylene glycol)-diacrylate fabricated inverted colloid crystal scaffold converted these immature progenitors into more advanced hepatic tissue structures. Hepatic constructs could also be successfully encapsulated into the immune-privileged material alginate and remained viable as well as functional upon transplantation into immune competent mice. This is the first report we are aware of demonstrating cGMP-compliant hPSCs can generate cells with advanced hepatic function potentially suitable for future therapeutic applications. Stem Cells Translational Medicine 2019;8:124&14 : Abstract :